PENGARUH JENIS KAPANG DAN PENAMBAHAN Lactobacillus plantarum KIK TERHADAP MUTU SUFU - . Nurhayati; Betty Sri Laksmi Jenie; Harsi D. Kusumaningrum (JURNAL AGROTEKNOLOGI, 2007)
Sufu is a traditional Chinese fermented soybean curd (tofu) resembling a soft creamy cheese-type product. It is made by fungal solid-state fermentation of tofu followed by aging in saturated brine solution. The aims of the research were to obtain the best indigenous mold strain for sufu fermentation and to produce the low salt sufu by applying Lactobacillus plantarum kik during aging. Four indigenous mold strains were used i.e Rhizopus oligosporus, R. oryzae, Mucor hiemalis and Actinomucor elegans. To produce the low salt sufu, the salt concentrations applied were varied in the range of 6% - 12% and by combination of 3% (v/v) L. plantarum kik. The results showed that the fermentation time of pizi was influenced by the mold species. Further sensory evaluation (Balance Incomplete Block Rating Design) on the hedonic rating of sufu revealed that aging in 9% brine and application of 3% (v/v) L. plantarum kik produced the most preferred sufu by the panelists. Combination of L. plantarum kik and pasteurization of sufu could maintain the quality for three weeks. Keywords: pizi, sufu, fungal, Lactobacillus plantarum kik